Isokinetic testing of muscle strength of older individuals with sarcopenia or frailty: A systematic review - Steffl, Michal; Stastny, Petr (Isokinetics and exercise science, 2020)
BACKGROUND : Sarcopenia is a component of frailty, which is a common geriatric syndrome for which the quantification of muscle strength is important. OBJECTIVE: Describe studies that have used isokinetic testing for detecting sarcopenia and determine whether there is an isokinetic strength level that can best detect sarcopenia. METHODS : A systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Our literature search involved the following key words: (isokinet*) AND ((sarcopenia) OR (frailty) OR (muscle weakness). Sarcopenia reference values for isokinetic knee flexion and extension at 60 ∘ /s were determined using summary data from relevant articles. RESULTS: A total of 19 studies that were relevant and lacked major methodological flaws were included. Most measured peak torque of the knee extensors and/or flexors. The measurements were found to be valid and responsive. The net moment weighted averages for knee extension torques were 83 ± 3 Nm for males and 60 ± 7 Nm for females in sarcopenia population. For knee flexion, the weighted averages for knee extension torque were 47 ± 6 Nm for males and 36 ± 5 Nm for females in sarcopenia population. All weighted averages were significantly lower than the reference values for the healthy population aged 60–70 ( p < 0.001). CONCLUSIONS: The isokinetic strength values reported herein can be used to identify sarcopenia in older men and women.